Presumed gabapentin-induced myoclonus in two cats - Caroline Buckley; Croix Griffin; Heather Anderson; Sarah A Moore (Journal of Feline Medicine and Surgery Open Reports)
Case series summary This case report describes the history and presentation of two cats with presumed gabapentin-induced myoclonus. Although this phenomenon is well documented in people, there are no previous reports in cats. Both cats in the current report had International Renal Interest Society (IRIS) stage 2 chronic kidney disease, a history of seizures (one generalized, one focal), and received gabapentin before veterinary hospital visits to alleviate anxiety (doses in the range of 11.8–16.4 mg/kg). While in the hospital, both cats were noted to have intermittent short jerks of the head that were different from the seizure activity previously noted by their owners at home. These cases appear to be the first published reports of this potential adverse effect of gabapentin in cats and risk factors in the present cases mirror those described in people. Relevance and novel information Clinicians should be aware of the potential for this phenomenon in cats receiving recommended doses of gabapentin, and future studies should focus on the role of chronic kidney disease and other neurologic conditions as risk factors for development of this condition.